Environmental pesticide distribution in horticultural and floricultural periurban production units - Querejeta, Giselle Andrea (2012)
The environmental pesticide distribution on non-target systems (soil, drift and agricultural plastics) during the application stage in small periurban production units (open field and greenhouses), was studied for various crops (tomato, lettuce, broccoli, strawberry and flowers) using different pesticides (endosulfan, procymidone, chlorothalonil, chlorpyrifos and deltamethrin). In all cases, soil was the most exposed non-target system. For greenhouses, a general pesticide distribution was found of approximately 2/3 for crop, 1/4 for soil and 1/20 for plastic, of the total amount applied. In horticultural open fields, although the distribution was very dependent on the crop size and type, soil was also the most exposed non-target subsystem. Pesticide drift seems not to be significant in these production units, whilst pesticide accumulation on agricultural plastics reached up to 45% of the total applied, for polyethylene mulching in strawberry fields.